A significação jornalística da justiça : uma análise da cobertura da Lava Jato na Folha de S. Paulo - Augsten, Patrícia (2019)
The present study has the objective to present the results of a research in which the goal is to analyze the process of publicist meaning of the legal sphere as of the Lava Jato operation, triggered in 2014. This research is restricted to the journalist pieces from Poder, a segment of the newspaper Folha de S. Paulo, utilizing seven pre-defined time frames, divided in three big periods: 1) The Pre-Lula era, 2) Lula’s Judgment, 3) Lula’s conviction and imprisonment. In total, 287 pieces regarding the Lava Jato operation were analyzed, in 10 weeks of investigation, between 2014 and 2018. Our theoretical foundation is embodied with the marxist theory of language, proposed by the Russian semiologist Mikhail Bakhtin. We approach the concepts of meaning and significance of enunciation and speech, which allowed a theoretical-practical support for the newspaper’s pieces analysis. We also propose a brief reference to the role of journalism and justice in Brazil, as well as a reflection in regard of the relation between them. The body of the research appreciation reveals that the news production process utilizes types of speeches that present itself as being the truth, and above all, trying to make the point of view of the newspaper to be accepted. Among the results achieved, we highlight that, during the Lava Jato operation, there was a huge change of speech in Folha de S. Paulo, in what is related to the legal sphere agents. This happens at the same time as the investigation gets closer to emblematic and popular political figures, such as the former president Luiz Inácio Lula da Silva.